Os lobbies no processo constituinte 1987-88 - Costa, Lucas Nascimento Ferraz (2017)
This research is based on the hypothesis that the more progressive and detailed constitutions tend to be the result of drafting processes marked by a high level of popular participation. We analyze this relationship based on the 1987-88 drafting process. We present an interpretation on the lobby during the period, proposing an organizational model for the interest groups in the process. We argued that the lobby was translated into the division between two types of interest groups, defined by the product of the relationship between their organizational characteristics and the area of interest in which they were inserted. This dynamic constitutes a theoretical model defined by the tendency of centralization of interests in a single group, which represented, formally or not, all other groups in each area of interest. The model was based on an empirical analysis of the interest groups' performance in the areas of Education and Health Care, whose relationship revealed the occurrence of the organizational model, which we express through network analysis.